Associations between expression levels of O-GlcNAc transferase (OGT) and chemo-response in osteosarcoma - S. Rattanakuntee (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND Objective: The present study aimed to investigate global levels of O-GlcNAcylation (O-GlcNAc), expressions of O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA) in osteosarcoma and to explore a prognostic marker. Materials and Methods: The authors studied in three independent experiments. Western blot analysis was performed to detect the expressions of O-GlcNAcylated proteins, OGT, and OGA in cell lines derived from seven patients with osteosarcoma stage IIB. The band intensities were analyzed using Scion Image software. The correlations between clinicopathologic characters of osteosarcoma cases and expression levels of O-GlcNAcylated proteins, OGT, and OGA were analyzed by using Student’s t-test. Results: The results demonstrated a tendency of higher OGT expression in primary osteosarcoma cells. Furthermore, the level of OGT was elevated in patients who poorly responded to chemotherapy and had shorter survival time (p<0.05). The present study revealed a promising use of OGT as a prognostic marker in osteosarcoma. Conclusion: The present study showed significant higher levels of OGT in osteosarcoma patients who poorly responded to chemotherapy. Furthermore, levels of OGT relate to survival time of osteosarcoma. These findings suggest a role for OGT in chemo-response of osteosarcoma cells. The present study was performed in a limited number of cases, thereby the finding requires further validation in a larger cohort.